Coal dust suppressant and preparation method thereof
By using coal dust suppressants composed of separately stored components A and B, and forming a shell film with polyacrylic acid resin and fiber particles, the problems of unclear color development and insufficient wind erosion resistance during coal transportation are solved, achieving a clear color development and efficient dust suppression effect.
Patent Information
- Application Number
- CN202511672109.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-14
- Publication Date
- 2026-01-09
AI Technical Summary
Dust pollution is a problem in the current coal transportation process. In particular, under high wind speed conditions, the dust suppressant does not show obvious color and has insufficient wind erosion resistance, resulting in uneven spraying and waste of resources.
The coal dust suppressant is composed of separately stored components A and B. Component A consists of liquid polyacrylic acid resin and stabilizer, while component B consists of solid pigments, fiber particles and thickener. It forms a shell membrane through a cross-linked network structure to capture dust particles, and has obvious color development and is resistant to wind erosion.
It achieves clear color development and uniform spraying during coal transportation, reduces resource waste, effectively suppresses dust under high wind speeds, and possesses high-strength adhesion and durability.
Smart Images

Figure CN121293825A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer coatings, specifically relating to a coal dust suppressant, its preparation method, and its application. Background Technology
[0002] my country has abundant coal resources, but their distribution is severely uneven, leading to a coal transportation network of "north-to-south coal transport" and "west-to-east coal transfer." Currently, open-top railway transport remains the main form of coal transportation. During coal transportation, especially long-distance transport, open-top transport causes coal dust pollution, resulting in air, soil, and water pollution in the surrounding environment. A common dust suppression method is spraying dust suppressants. Publications CN115181546A (published on October 14, 2022), CN109609093A (published on April 12, 2019), CN112210020A (published on January 12, 2021), and CN112920776A (published on June 8, 2021) all document coal dust suppressants. However, existing dust suppressants are all colorless, making it difficult to quickly and accurately identify coal seams that are not properly sprayed; remedial spraying often results in overspraying, leading to resource waste. Therefore, dust suppressants that can color coal seem to solve the above problems. However, when coal particles are piled up, there are large gaps between them. Pigment particles dissolved or dispersed in the dust suppressant solution can easily penetrate through these gaps, resulting in indistinct color development after spraying or requiring the addition of large amounts of pigment to achieve a noticeable color. Furthermore, common inorganic pigments tend to settle rapidly in dust suppressants, making it difficult to maintain the stability of the solution within the limited 2-3 hour spraying time. While organic pigments have better compatibility, they are more expensive. Additionally, white is the most contrasting color against black coal, making it the preferred choice for coal coloring; however, white organic pigments tend to become transparent after soaking in aqueous solutions, resulting in indistinct color development.
[0003] Furthermore, with the acceleration of heavy-haul railway transportation, the relative speed between two trains exceeding 160 km / h during intersections, theoretically reaching wind speeds of 40 m / s and above; currently, the highest wind erosion resistance of dust suppressants is only tested at 30 m / s. Clearly, real-world scenarios place higher demands on the wind erosion resistance of dust suppressants.
[0004] Therefore, developing coal dust suppressants that combine colorimetric observation function with better wind erosion resistance is of great practical significance. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a coal dust suppressant, its preparation method, and its application. The dust suppressant of this invention uses polyacrylic acid resin as the binder for coal particles and a combination of fiber particles and pigments as the colorant, achieving color development with only a small amount of inorganic mineral pigments, thus not affecting coal combustion. Furthermore, the dust suppressant of this invention can effectively reduce wind erosion of bulk materials such as coal, especially during transportation.
[0006] To achieve the above-mentioned technical effects, the present invention adopts the following technical solution:
[0007] A coal dust suppressant is composed of two separately stored components, A and B, wherein component A is liquid and component B is solid, and the mass ratio of the two components is A:B = (1~5):1;
[0008] By weight, component A consists of 10-60 parts of polyacrylic acid resin and 0.1-3 parts of stabilizer, and component B consists of 3-10 parts of pigment, 4-12 parts of fiber particles and 0.5-3 parts of thickener;
[0009] The fiber particles have a mass that is 1-2 times the mass of the pigment; the fiber particles have a length of 0.2-2.0 mm; and the pigment has a particle size of 800-1200 mesh.
[0010] Preferably, the mass ratio of component A to component B is A:B = (1.2~5):1.
[0011] More preferably, the mass ratio of component A to component B is A:B = (1.5~4):1.
[0012] Preferably, the mass of the fiber particles is 1.1-1.7 times the mass of the pigment.
[0013] Preferably, component A consists of 10-50 parts of polyacrylic acid resin and 0.1-3 parts of stabilizer, by weight.
[0014] More preferably, component A consists of 20-50 parts of polyacrylic acid resin and 0.5-2 parts of stabilizer, by weight.
[0015] Preferably, the polyacrylic resin is selected from one or more polymers and copolymers of monomers such as acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate.
[0016] More preferably, the polyacrylic resin is selected from one or more of polyacrylic acid, hydroxyethyl polyacrylate, hydroxypropyl polyacrylate, polymethacrylic acid, polyhydroxyethyl methacrylate, acrylic acid-hydroxyethyl acrylate copolymer, acrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-hydroxypropyl methacrylate copolymer, methacrylic acid-hydroxyethyl acrylate copolymer, methacrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-hydroxyethyl acrylate-hydroxypropyl methacrylate copolymer, acrylic acid-hydroxyethyl acrylate-hydroxyethyl methacrylate copolymer, acrylic acid-methacrylic acid-hydroxyethyl methacrylate copolymer, and acrylic acid-methacrylic acid-hydroxypropyl methacrylate copolymer.
[0017] Most preferably, the polyacrylic resin is selected from one or more of the following: acrylic acid-hydroxyethyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-hydroxyethyl methacrylate-hydroxyethyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate-hydroxyethyl acrylate copolymer, acrylic acid-hydroxyethyl acrylate-hydroxyethyl methacrylate copolymer, and calcium acrylate-hydroxyethyl methacrylate-hydroxyethyl acrylate copolymer.
[0018] Preferably, the polyacrylic acid resin has a weight-average molecular weight of 2,000-200,000.
[0019] More preferably, the polyacrylic acid resin has a weight-average molecular weight of 3,000-100,000.
[0020] The polypropylene resin described in this invention is a viscous aqueous liquid with a solid content of 25% to 60%, and can be obtained through commercial purchases.
[0021] Preferably, the stabilizer is composed of an organic base and a corrosion inhibitor in a mass ratio of (2-10):1.
[0022] More preferably, the stabilizer is composed of an organic base and a corrosion inhibitor in a mass ratio of (4-7):1.
[0023] Preferably, the organic base is selected from one or more of ethanolamine, diethanolamine, triethanolamine, triethanolamine borate, and silicated triethanolamine.
[0024] More preferably, the organic base is selected from one or more of triethanolamine, triethanolamine borate, and silicated triethanolamine.
[0025] Preferably, the corrosion inhibitor is selected from one or more of benzotriazole and its derivatives, benzothiazole and its derivatives, imidazoline and its derivatives, and imidazole and its derivatives.
[0026] More preferably, the corrosion inhibitor is selected from one or more of benzothiazole and its derivatives.
[0027] Preferably, component B, by weight, consists of 4-8 parts pigment, 4-10 parts fiber particles, and 0.5-2 parts thickener.
[0028] The pigment is selected from one or more of titanium dioxide, light calcium carbonate, lithopone, iron yellow powder, basic cyanine blue, acid red, and fruit green powder.
[0029] Preferably, the fiber particles are selected from one or more of wood fiber particles, bamboo fiber particles, straw fiber particles, pulp fiber particles, and ink-free recycled paper fiber particles.
[0030] More preferably, the fiber particles are pulp fibers.
[0031] Preferably, the thickener is selected from one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, sodium carboxymethyl cellulose, polyacrylamide, polyethylene oxide (PEO), polyvinyl alcohol, and polyethylene glycol (PEG);
[0032] More preferably, the thickener is selected from one or more of hydroxyethyl cellulose, hydroxypropyl cellulose, sodium carboxymethyl cellulose, polyacrylamide, and polyethylene oxide.
[0033] The present invention also provides a method for preparing the above-mentioned coal dust suppressant, including material preparation, preparation of component A and component B respectively, and separate sealed storage.
[0034] Specifically, the preparation method of the coal dust suppressant includes the following steps:
[0035] S1. Prepare all raw materials according to the proportions;
[0036] S2. Preparation of Component A
[0037] The polyacrylic acid resin and stabilizer are mixed according to the specified ratio, stirred evenly, and then transferred to a storage container, sealed and stored to obtain the final product.
[0038] S3. Preparation of Component B
[0039] The pigment, fiber particles, and thickener are mixed evenly according to the specified ratio and stored in a sealed container to obtain the final product.
[0040] Preferably, in step S2, the polyacrylic acid resin and stabilizer are stirred and mixed in a high-speed dispersion mixing tank for 10-30 minutes at a speed of 200-900 rpm.
[0041] Preferably, in step S3, the pigment, fiber particles and thickener are mixed in a dry powder mixer, a two-dimensional mixer or a three-dimensional mixer for 10-30 minutes; wherein, the rotation speed of the dry powder mixer can be set to 50-500 rpm, and the rotation speed of the two-dimensional mixer or the three-dimensional mixer can be set to 60-400 rpm.
[0042] Another object of the present invention is to provide a method for using the coal dust suppressant described in the present invention or the coal dust suppressant directly obtained by the above preparation method, comprising the following steps:
[0043] I. Take component A and component B respectively according to the mass ratio A:B = (1~5):1, mix them, add water with a mass ratio of 30-150 times that of component B, stir evenly to obtain a dust suppressant solution;
[0044] II. Spray the dust suppressant solution obtained in step I evenly onto the bulk material and allow it to dry naturally.
[0045] Preferably, in step I, the mass of water is 70-110 times the mass of component B.
[0046] Preferably, the bulk materials include, but are not limited to, coal, fine ore powder, and fine sand.
[0047] The dust suppressant solution of this invention will show color immediately upon spraying onto bulk powders such as coal. Therefore, operators can visually judge whether the dust suppressant solution is sprayed evenly, facilitating control of the spraying amount and avoiding under- or over-spraying. Generally, the spraying rate of the dust suppressant solution of this invention is 1.0-4.0 L / m³. 2 .
[0048] The dust suppressant of this invention consists of two separately stored components, A and B. The polyacrylic acid resin in component A and the thickener in component B have carboxyl and hydroxyl functional groups in their molecular structures that interact through hydrogen bonds to form a cross-linked network structure. Simultaneously, these molecules also contain carboxyl and amino groups, which, due to their high charge density, exhibit strong affinity with groups carrying opposite charges. Ultimately, through coagulation and adhesion, they rapidly capture and adsorb dust particles, and after drying, they form a shell with a certain strength with the dust particles.
[0049] The dust suppressant of this invention uses a composite of pigments and fiber particles with a particle size of 800-1200 mesh in component B, which is then added to the polyacrylic acid resin system (component A). This effectively solves the problem of unclear color development due to large gaps between coal particles, enabling direct visual observation of the dust suppressant's spray coverage effect and direct monitoring during coal transportation. It also avoids the impact of using large amounts of inorganic pigments on coal combustion performance. Furthermore, the fiber particles ensure good stability of the dust suppressant solution, allowing for sufficient preparation and spraying time. Simultaneously, the overlapping effect between the fiber particles easily covers the large gaps between coal particles, thus achieving a significant color development effect even with a small amount of pigment.
[0050] The dust suppressant of this invention is used during the transportation and stockpiling of bulk materials such as coal and fine ore. Because it has a colorimetric observation function, it can effectively determine whether the spraying is adequate and its effectiveness during application, allowing for timely remedial spraying and reducing unnecessary respraying. The dust suppressant of this invention also has high adhesive strength and durability, effectively preventing severe dust generation during strong winds. Therefore, the dust suppressant of this invention offers significant environmental and social benefits.
[0051] In this application, the mass fractions of each component represent the mass ratio between the components. Depending on the actual situation, 1 mass fraction can be any mass number, such as 1g, 5g, 10g, 50g, 250g, 500g, 1kg, 1 ton, 10 tons, etc. Attached Figure Description
[0052] The present invention will now be further described with reference to the accompanying drawings.
[0053] Figure 1 The photograph shows the surface of coal that has just been sprayed with the coal dust suppressant solution of Example 28.
[0054] Figure 2 The photograph shows the coal dust suppressant solution of Example 28 after it has solidified on the coal surface.
[0055] Figure 3 The photos show the coloring effect of the dust suppressant solution on coal in Comparative Example 9. The left photo shows the coal surface before spraying the dust suppressant solution, and the right photo shows the coal surface after spraying the dust suppressant solution.
[0056] Figure 4 The photos show the coloring effect of the dust suppressant solution on coal in Comparative Example 10. The left photo shows the coal surface before spraying the dust suppressant solution, and the right photo shows the coal surface after spraying the dust suppressant solution. Detailed Implementation
[0057] This invention provides a coal dust suppressant, which consists of two separately stored components, A and B, wherein component A is liquid and component B is solid, and the mass ratio of the two components is A:B = (1~5):1;
[0058] By weight, component A consists of 10-60 parts of polyacrylic acid resin and 0.1-3 parts of stabilizer, and component B consists of 3-10 parts of pigment, 4-12 parts of fiber particles and 0.5-3 parts of thickener;
[0059] The mass of the fiber particles is 1-2 times the mass of the pigment, preferably 1.1-1.7 times;
[0060] The pigment is selected from one or more of titanium dioxide, light calcium carbonate, lithopone, iron yellow powder, basic blue, acid red and fruit green powder, with a particle size of 800 mesh-1200 mesh.
[0061] The length of the fiber particles is 0.2-2.0 mm.
[0062] The stabilizer is composed of an organic base and a corrosion inhibitor in a mass ratio of (2-10):1, preferably (4-7):1.
[0063] The present invention will be described below with reference to specific embodiments. Those skilled in the art will understand that these embodiments are for illustrative purposes only and do not limit the scope of the invention in any way.
[0064] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, all raw materials and reagents used in the following examples are commercially available products. The purchase details of some raw materials are as follows:
[0065] Polyacrylic acid, calcium polyacrylate, magnesium polyacrylate, polymethacrylic acid, hydroxyethyl polyacrylate, hydroxyethyl methacrylate, acrylic acid-hydroxyethyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-methacrylate-hydroxyethyl methacrylate copolymer, acrylic acid-methacrylate-hydroxyethyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate-hydroxyethyl acrylate copolymer, calcium acrylate-methacrylate-hydroxyethyl acrylate copolymer: solid content 25%~60%, Nanjing Zhenzhi New Material Technology Co., Ltd.;
[0066] Polyvinyl alcohol, hydroxyethyl cellulose, hydroxypropyl cellulose, sodium carboxymethyl cellulose, polyacrylamide, polyethylene oxide (molecular weight 800w-1200w): Beijing Qianmen Chemical Co., Ltd.
[0067] Triethanolamine, Triethanolamine Borate, Silicated Triethanolamine, Imidazolium Corrosion Inhibitor 168, Imidazole Corrosion Inhibitor 112, Benzotriazole Corrosion Inhibitor 121, Benzothiazole Corrosion Inhibitor 131: Beijing Qianmen Chemical Co., Ltd.;
[0068] Titanium dioxide, light calcium carbonate, lithopone, iron oxide yellow powder, basic cyanide blue, acid red and fruit green powder: Hebei Lingqiao Chemical Co., Ltd., of which the particle size of titanium dioxide, light calcium carbonate, lithopone and iron oxide yellow powder is 800 mesh-1200 mesh;
[0069] Wood fiber, pulp fiber, bamboo fiber, recycled paper fiber (including ink): particle length 0.2-2.0 mm, Shandong Leiming International Trade Co., Ltd.
[0070] In the following examples and comparative examples, components A and B were prepared using the following steps and processes:
[0071] S1. Prepare all raw materials according to the proportions.
[0072] S2. Preparation of Component A
[0073] The polyacrylic acid resin and stabilizer are added to a high-speed dispersion mixing tank according to the specified ratio. The mixture is stirred at 200-900 rpm for 10-30 minutes. Then, it is transferred to a storage container, sealed and stored. The product is ready for use.
[0074] S3. Preparation of Component B
[0075] Add the pigment, fiber particles and thickener to a dry powder mixer (50-500 rpm), a two-dimensional mixer or a three-dimensional mixer (60-400 rpm), mix for 10-30 minutes, seal and store for later use.
[0076] Before use, mix components A, B, and water according to the specified ratio to obtain a dust suppressant solution.
[0077] Examples 1-8 Research on a coal dust suppressant—polyacrylic acid resin
[0078] The coal dust suppressant described in Examples 1-8 consists of a liquid component A and a solid component B, which are stored separately. The raw material composition of the two components is shown in Table 1, where 1 part by mass = 1 kg. Before use, component A, component B, and water are mixed evenly according to the parts by mass shown in Table 1 to obtain a dust suppressant solution.
[0079]
[0080] The wind erosion rate, solution stability, solution hiding power, and cured layer strength of the dust suppressant solutions in Examples 1-8 were measured respectively. Specifically, the wind erosion rate at high speed (40 m / s), the compressive strength of the cured layer (cured layer strength), and the solution hiding power were measured according to the following methods:
[0081] a) Wind erosion rate at high wind speeds
[0082] The test method refers to TB / T 3210.1-2020 "Technical Conditions for Dust Suppression in Railway Coal Transportation Part 1: Dust Suppressants". The test samples were cured for 2 hours at room temperature and 50℃ respectively. The wind speeds for the wind erosion test were 30 m / s and 40 m / s respectively. The samples were weighed before and after the erosion test to obtain the mass loss of coal after erosion.
[0083] Formula for calculating wind erosion rate: R=(m1-m2) / (m1-m0)
[0084] In the formula, R represents the wind erosion rate (%).
[0085] m0 — Weight of empty disk (g)
[0086] m1 — Total weight (g) of coal, dust suppressant, and empty pan before erosion.
[0087] m2 — Total weight (g) of coal, dust suppressant and empty disc after erosion.
[0088] The TB / T 3210.1-2020 standard specifies that the wind erosion rate shall not exceed 1%.
[0089] b) Compressive strength of the cured layer
[0090] The sample preparation method refers to TB / T 3210.1-2020 "Technical Conditions for Dust Suppression in Railway Coal Transportation Part 1: Dust Suppressants". The test samples were cured for 2 hours at room temperature and 50℃ respectively. The compressive strength was measured using a thrust gauge (Note: the contact area of the force gauge used in this application is 28 mm). 2 The test is conducted by selecting at least 5 points at different locations on the sample to test its average maximum breaking force, which is recorded as the compressive strength (N).
[0091] c) Solution covering power
[0092] The hiding power of the dust suppressant solution was tested according to the test method in GB / T 23981.2 "Determination of Hiding Power of Paints and Varnishes Part 2: Black and White Grid Method". The test method is as follows: Add an appropriate amount of sample to a cup, place a dropper into the cup, and weigh the total mass (m2) of the cup containing the sample and the dropper, accurate to 1 mg. Use the dropper to evenly drop the sample onto the black and white grid glass plate. The dropping should be rapid and uniform, and the sample should not be dropped outside the grid area. After the dropping is complete, immediately place the plate in the center of a dark box placed against the light, 15 cm to 20 cm away from the frosted glass. Observe the plate visually under one and two fluorescent lamps, respectively, until the black and white grid is just barely visible. Then weigh the total mass (m3) of the cup containing the remaining sample and the dropper, accurate to 1 mg. Perform the test twice in parallel. The results are expressed as follows:
[0093] The shielding force X0 of the sample, expressed in g / cm³ 2 It is indicated that the following formula is used for calculation:
[0094] X0 = (m2 - m3) / S * 10 4
[0095] in:
[0096] m2—The total mass of the sample, cup, and dropper before brushing, in grams;
[0097] m3—The total mass of the sample, cup, and dropper after brush coating, in grams;
[0098] S — The area of the sample dropped onto the black and white checkered plate, in cm². 2 .
[0099] The smaller the value, the stronger the hiding power of the solution.
[0100] The measurement results are shown in Table 2.
[0101]
[0102] Table 2 shows that the dust suppressant solutions of Examples 1-8 exhibited comparable stability, hiding power, and cured layer strength. However, the dust suppressants using methacrylic acid and hydroxyethyl acrylate monomers as polypropylene resins (Examples 1 and 2) showed inferior wind erosion resistance compared to the copolymer systems. Among the copolymer-containing dust suppressants, Example 6 demonstrated the best overall performance. Therefore, in subsequent examples investigating other components of the dust suppressants, the polyacrylic acid resin was always an acrylic acid-methacrylic acid-hydroxyethyl acrylate copolymer.
[0103] Examples 9-18 Research on a coal dust suppressant-stabilizer combination
[0104] The coal dust suppressant described in Examples 9-18 consists of a liquid component A and a solid component B, which are stored separately. The raw material composition of the two components is shown in Table 3, where 1 part by mass = 1 kg. Before use, component A, component B, and water are mixed evenly according to the parts by mass shown in Table 3 to obtain a dust suppressant solution.
[0105] The dust suppressant solutions of Examples 9-18 were tested for wind erosion rate, solution stability, solution hiding power, and cured layer strength according to the aforementioned methods; their corrosivity to metals was also tested according to the following methods:
[0106] The test was conducted according to the method specified in JB / T7901. The test pieces were placed in a sealed glass container filled with a dust suppressant solution and immersed for 168 hours at an ambient temperature of (20±5)℃. The arithmetic mean of three test samples for each material was taken as the test result.
[0107] According to the standard, the average corrosion rate of Q450NQR1 steel should be ≤0.05mm / a, the average corrosion rate of 5083 aluminum alloy should be ≤0.03mm / a, and the average corrosion rate of T4003 stainless steel should be ≤0.005mm / a.
[0108] The measurement results are shown in Table 4.
[0109]
[0110]
[0111] Table 4 shows that in a polyacrylic acid resin system where the resin is an acrylic acid-methacrylic acid-hydroxyethyl acrylate copolymer, the dust suppressant performance of Examples 9-16 is comparable when the pigment dosage is the same. Considering the low price and significant cost-effectiveness of triethanolamine, it was chosen as the organic base for subsequent examples. When benzothiazole corrosion inhibitor 131 was combined with triethanolamine (Examples 16-18), the dust suppressant solution exhibited the lowest corrosion rate and superior rust prevention performance against Q450NQR1 steel. Therefore, triethanolamine and benzothiazole corrosion inhibitor 131 were selected as the stabilizer combination for subsequent studies.
[0112] Examples 19-28 Research on Component B of a Coal Dust Suppressant I
[0113] The coal dust suppressant described in Examples 19-28 consists of a liquid component A and a solid component B, which are stored separately. The raw material composition of the two components is shown in Table 5, where 1 part by mass = 1 kg. Before use, component A, component B, and water are mixed evenly according to the parts by mass shown in Table 5 to obtain the dust suppressant solution.
[0114]
[0115] The dust suppressant solutions of Examples 19-28 were tested for wind erosion rate, solution stability, solution covering power and cured layer strength, and the results are shown in Table 6.
[0116] Table 6 shows that titanium dioxide, iron oxide yellow, fruit green, basic magenta, acid red, and combinations of titanium dioxide with other dark pigments are all suitable for color development in dust suppressant solutions. When the amount of pigment is the same, the dust suppressant performance of Examples 19-24 is comparable; the color development effect depends on the different colors resulting from the different pigment types, corresponding to differences in the hiding power of the dust suppressant solution. Examples 25-26 respectively show the addition of pulp fiber and bamboo fiber to the dust suppressant solution. The dust suppressant solution with added pulp fiber exhibits further improved stability compared to those with wood fiber and bamboo fiber, extending the storage time of the dust suppressant solution.
[0117] When the dust suppressant solution of Example 28 is sprayed onto coal, the coal appears distinctly white, completely covering its original black color; see details below. Figure 1 As shown in the photo, after curing, a distinct white layer is clearly visible on the coal surface, indicating that the dust suppressant curing layer has covered the entire surface of the coal; see details... Figure 2 As shown in the photo.
[0118]
[0119] Examples 29-38 A Study on Component B of a Coal Dust Suppressant II
[0120] The coal dust suppressant described in Examples 29-38 consists of a liquid component A and a solid component B, which are stored separately. The raw material composition of the two components is shown in Table 7, where 1 part by mass = 1 kg. Before use, component A, component B, and water are mixed evenly according to the parts by mass shown in Table 7 to obtain a dust suppressant solution.
[0121]
[0122] The dust suppressant solutions of Examples 29-38 were tested for wind erosion rate, solution stability, solution failure probability and cured layer strength, and the results are shown in Table 8.
[0123]
[0124] Table 8 shows that different combinations of titanium dioxide, iron oxide yellow, fruit green powder, basic blue, acid red, and pulp fiber have varying effects on the stability, hiding power, and cured layer strength of the dust suppressant solution. The dust suppressant solution exhibits the best hiding power when the mass of pulp fiber is approximately 1 to 2 times the mass of the pigment. While increasing the amount of pulp fiber increases the cured layer strength, it slightly decreases the stability of the dust suppressant solution.
[0125] Examples 39-44 A coal dust suppressant
[0126] Examples 1-38 optimized the composition of the coal dust suppressant of the present invention. Examples 39-44 investigated the effects of different dosage ratios of these components and different amounts of water added on the performance of the dust suppressant.
[0127] The coal dust suppressant described in Examples 39-44 consists of a liquid component A and a solid component B, which are stored separately. The raw material composition of the two components is shown in Table 8, where 1 part by mass = 1 kg. Before use, component A, component B, and water are mixed evenly according to the parts by mass shown in Table 8 to obtain the dust suppressant solution.
[0128] The dust suppressants of Examples 39-44 were tested for wind erosion rate, solution stability, solution covering power and cured layer strength, and the results are shown in Table 10.
[0129] Table 10 shows that for the coal dust suppressants of Examples 39-44, the higher the amount of polypropylene resin used, the lower the wind erosion rate and the better the dust suppression effect at the same wind speed; as the dilution ratio increases, the covering power and the strength of the cured layer of the dust suppressant decrease.
[0130]
[0131]
[0132] Comparative Examples 1-8: A coal dust suppressant
[0133] The coal dust suppressants described in Comparative Examples 1-8 consist of a liquid component A and a solid component B, which are stored separately. The raw material composition of the two components is shown in Table 9, where 1 part by mass = 1 kg. Before use, component A, component B, and water are mixed evenly according to the parts by mass shown in Table 11 to obtain a dust suppressant solution. Wherein:
[0134] In Comparative Example 1, the amount of acrylic acid-methacrylic acid-hydroxyethyl acrylate copolymer was only 10 parts by weight. Comparative Example 2 used sodium polyacrylate as the polypropylene resin. Comparative Example 3 contained no corrosion inhibitor. In Comparative Example 4, the mass ratio of pigment (titanium dioxide) to fiber particles (pulp fiber) was approximately 1:0.42. In Comparative Example 5, the mass ratio of pigment (titanium dioxide) to fiber particles (pulp fiber) was approximately 1:2.3. In Comparative Example 6, the fiber particles were polypropylene fibers. In Comparative Example 7, the fiber particles were recycled paper fibers containing ink. In Comparative Example 8, the thickener included 4 parts by weight of hydroxypropyl cellulose.
[0135]
[0136] For the dust suppressant solutions in Examples 1-8, the wind erosion rate, solution stability, solution hiding power, cured layer strength, and metal corrosivity were measured respectively. The metal corrosivity was determined using the following method:
[0137] The test was conducted according to the method specified in JB / T7901. The test pieces were placed in a sealed glass container filled with a dust suppressant solution and immersed for 168 hours at an ambient temperature of (20±5)℃. The arithmetic mean of three test samples for each material was taken as the test result.
[0138] According to the standard, the average corrosion rate of Q450NQR1 steel should be ≤0.05mm / a, the average corrosion rate of 5083 aluminum alloy should be ≤0.03mm / a, and the average corrosion rate of T4003 stainless steel should be ≤0.005mm / a.
[0139] The results are shown in Table 12.
[0140]
[0141] The data in Table 12 shows:
[0142] Except for Comparative Example 8, the cured layer strength of all other comparative examples was low, and the cured layer was easily damaged during long-distance transportation.
[0143] The amount of polyacrylic acid resin used as a dust suppressant in Comparative Example 1 was too small, resulting in a wind erosion rate of more than 1% at a wind speed of 40 m / s, which did not meet the standard requirement.
[0144] The dust suppressant in Comparative Example 2 used an acrylate polymer, and its wind erosion rate was also greater than 1% at a wind speed of 40 m / s, which also failed to meet the standard value.
[0145] The dust suppressant in Comparative Example 3 does not contain corrosion inhibitors and has strong corrosiveness to metals, making it unsuitable for use in railway open-top freight cars.
[0146] The working time of the dust suppressant was too short in Comparative Example 4 due to excessive use of inorganic pigments, in Comparative Example 5 due to excessive use of fiber particles, and in Comparative Examples 6 and 7 due to the use of inappropriate fiber particles.
[0147] The excessive amount of thickener in Comparative Example 8 resulted in excessive viscosity of the dust suppressant, leading to poor atomization during spraying.
[0148] Comparative Example 9 A dust suppressant solution
[0149] According to the product instructions, add 0.1 kg of Type I dust suppressant and 9.9 kg of water to a dispersion vessel and stir. Then add 0.8 kg of titanium dioxide pigment and continue stirring for 10-20 minutes to obtain the final product.
[0150] The prepared dust suppressant solution was sprayed onto the surface of the coal. After drying, the coloration of the coal surface was observed. Photos of the coal before and after spraying the dust suppressant are shown below. Figure 3 .
[0151] Figure 3 The photo on the left shows the coal before the dust suppressant was sprayed, while the photo on the right shows the coal after the dust suppressant was sprayed. Figure 3 It is clearly shown that most of the pigment in the dust suppressant of Comparative Example 9 penetrated into the spaces between coal particles, making it almost impossible to color the coal.
[0152] Comparative Example 10 A dust suppressant solution
[0153] According to the product instructions, add 0.1 kg of Type II dust suppressant and 9.9 kg of water to a dispersion vessel and stir. Then add 0.8 kg of titanium dioxide pigment and continue stirring for 10-20 minutes to obtain the final product.
[0154] The prepared dust suppressant solution was sprayed onto the surface of the coal. After drying, the coloration of the coal surface was observed. Photos of the coal before and after spraying the dust suppressant are shown below. Figure 4 .
[0155] Figure 4 The photo on the left shows coal before the dust suppressant was sprayed, and the photo on the right shows coal after the dust suppressant was sprayed. Figure 3 The situation shown is the same. Figure 4 It is clearly shown that most of the pigment in the dust suppressant of Comparative Example 10 also seeped into the spaces between coal particles, making it almost impossible to color the coal.
[0156] In summary, the dust suppressant provided by this invention achieves, for the first time, a visually apparent color change on the surface of coal. Furthermore, the dust suppressant exhibits excellent adhesion and dust suppression properties, with a wind erosion rate of less than 1.0 under wind speeds of 30 m / s and 40 m / s. Therefore, the dust suppressant of this invention can meet the dust suppression requirements for bulk materials such as coal and fine mineral powder during railway and highway transportation and stockpiling. Moreover, this dust suppressant demonstrates outstanding performance in high-wind-speed erosion and color observation.
Claims
1. A coal dust suppressant, comprising separately stored component A and component B, wherein component A is liquid and component B is solid, and the mass ratio of the two components is A:B = (1~5):1; By weight, component A consists of 10-60 parts of polyacrylic acid resin and 0.1-3 parts of stabilizer, and component B consists of 3-10 parts of pigment, 4-12 parts of fiber particles and 0.5-3 parts of thickener; in, The mass of the fiber particles is 1-2 times the mass of the pigment; the length of the fiber particles is 0.2-2.0 mm, and the particle size of the pigment is 800-1200 mesh.
2. The coal dust suppressant according to claim 1, characterized in that, The mass ratio of component A to component B is A:B = (1.2~5):1; Preferably, the mass ratio of component A to component B is A:B = (1.5~4):
1.
3. The coal dust suppressant according to claim 1, characterized in that, The mass of the fiber particles is 1.1 to 1.7 times the mass of the pigment.
4. The coal dust suppressant according to claim 1, characterized in that, By weight, component A consists of 10-50 parts of polyacrylic acid resin and 0.1-3 parts of stabilizer; Preferably, component A consists of 20-50 parts of polyacrylic acid resin and 0.5-2 parts of stabilizer, by weight.
5. The coal dust suppressant according to claim 1 or 4, characterized in that, The polyacrylic resin is selected from one or more polymers and copolymers thereof using acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate as monomers. Preferably, the polyacrylic resin is selected from one or more of the following: polyacrylic acid, hydroxyethyl polyacrylate, hydroxypropyl polyacrylate, polymethacrylic acid, polyhydroxyethyl methacrylate, acrylic acid-hydroxyethyl acrylate copolymer, acrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-hydroxypropyl methacrylate copolymer, methacrylic acid-hydroxyethyl acrylate copolymer, methacrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-hydroxyethyl acrylate-hydroxypropyl methacrylate copolymer, acrylic acid-hydroxyethyl acrylate-hydroxyethyl methacrylate copolymer, acrylic acid-methacrylic acid-hydroxyethyl methacrylate copolymer, and acrylic acid-methacrylic acid-hydroxypropyl methacrylate copolymer. Most preferably, the polyacrylic resin is selected from one or more of the following: acrylic acid-hydroxyethyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-hydroxyethyl methacrylate-hydroxyethyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate-hydroxyethyl acrylate copolymer, acrylic acid-hydroxyethyl acrylate-hydroxyethyl methacrylate copolymer, and calcium acrylate-hydroxyethyl methacrylate-hydroxyethyl acrylate copolymer. Preferably, the weight-average molecular weight of the polyacrylic acid resin is 2000-200000; More preferably, the polyacrylic acid resin has a weight-average molecular weight of 3,000-100,000.
6. The coal dust suppressant according to claim 1 or 4, characterized in that, The stabilizer is composed of an organic base and a corrosion inhibitor in a mass ratio of (2-10):1; Preferably, the stabilizer is composed of an organic base and a corrosion inhibitor in a mass ratio of (4-7):1; Preferably, the organic base is selected from one or more of ethanolamine, diethanolamine, triethanolamine, triethanolamine borate, and silicated triethanolamine; More preferably, the organic base is selected from one or more of triethanolamine, triethanolamine borate, and silicated triethanolamine; Preferably, the corrosion inhibitor is selected from one or more of benzotriazole and its derivatives, benzothiazole and its derivatives, imidazoline and its derivatives, and imidazole and its derivatives; More preferably, the corrosion inhibitor is selected from one or more of benzothiazole and its derivatives.
7. The coal dust suppressant according to claim 1, characterized in that, By weight, component B consists of 4-8 parts pigment, 4-10 parts fiber particles and 0.5-2 parts thickener.
8. The coal dust suppressant according to claim 1 or 7, characterized in that, The pigment is selected from one or more of titanium dioxide, light calcium carbonate, lithopone, iron yellow powder, basic cyanine blue, acid red, and fruit green powder; Preferably, the fiber particles are selected from one or more of wood fiber particles, bamboo fiber particles, straw fiber particles, pulp fiber particles and ink-free recycled paper fiber particles; More preferably, the fiber particles are pulp fibers; Preferably, the thickener is selected from one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, sodium carboxymethyl cellulose, polyacrylamide, polyethylene oxide, polyvinyl alcohol, and polyethylene glycol; More preferably, the thickener is selected from one or more of hydroxyethyl cellulose, hydroxypropyl cellulose, sodium carboxymethyl cellulose, polyacrylamide, and polyethylene oxide.
9. The method for preparing the coal dust suppressant according to any one of claims 1 to 8, comprising preparing raw materials, preparing component A and component B separately, and storing them separately in sealed containers; Specifically, the preparation method of the coal dust suppressant includes the following steps: S1. Prepare all raw materials according to the proportions; S2. Preparation of Component A The polyacrylic acid resin and stabilizer are mixed according to the specified ratio, stirred evenly, and then transferred to a storage container, sealed and stored to obtain the final product. S3. Preparation of Component B The pigment, fiber particles, and thickener are mixed evenly according to the specified ratio, and then stored in a sealed container to obtain the final product. Preferably, in step S2, the polyacrylic acid resin and the stabilizer are stirred and mixed in a high-speed dispersion mixing tank for 10-30 minutes at a speed of 200-900 rpm; Preferably, in step S3, the pigment, fiber particles, and thickener are mixed in a dry powder mixer, a two-dimensional mixer, or a three-dimensional mixer for 10-30 minutes; wherein, The speed of a dry powder mixer is 50-500 rpm, while the speed of a two-dimensional or three-dimensional mixer is 60-400 rpm.
10. A method of using the coal dust suppressant according to any one of claims 1 to 8, or the coal dust suppressant directly obtained by the preparation method according to claim 9, comprising the following steps: I. Take component A and component B respectively according to the mass ratio A:B = (1~5):1, mix them, add water with a mass ratio of 30-150 times that of component B, stir evenly to obtain a dust suppressant solution; II. Spray the dust suppressant solution obtained in step I evenly onto the bulk material and allow it to dry naturally; Preferably, in step I, the mass of water is 70-110 times the mass of component B; Preferably, the bulk material is selected from coal, fine mineral powder, or fine sand.
Citation Information
Patent Citations
Coal dust suppressant and use method thereof
CN109609093A
Preparation method and application of high-amylose starch capable of rapidly dissolving in cold water
CN112210020A
Coal dust suppressant and preparation method thereof
CN112920776A
Dust suppressant for railway coal transportation and preparation method thereof
CN115181546A